Validation of information system project success model: a focus group study - Subiyakto, A'ang; Ahlan, Abdul Rahman; Jaya Putra, Sopiyanshah; Kartiwi, Mira (SAGE Publications Inc., 2015)
This article illustrates how influential arguments were used to validate an information system (IS) project success model using the inductive-qualitative method rather than continual hypothesis testing. The purpose of the study was to explore the validity and feasibility of the model using a focus group study (FGS) to respond that many IS scholars were under more and more pressure in their research model validations. Most of them claimed that the quantitative validation was only the method to validate their models. Although they may have performed the qualitative validation, only a few of them realized that they have applied this method. This article will be valuable, especially to prove, describe, and illuminate the context and condition where the model validation had been performed qualitatively before the scholar carried out quantitatively the validation. The results represent the four model validation points regarding the modeling process, methodological aspect, and resource availability of the research and its implementation recommendations. A good reference point for IS scholars whose goal to validate their model feasibilities, especially using the qualitative validation method.